Medical Education- Teaching and Learning - Osman, Hafiz Elshazali; Elshazali, Osama Hafiz (Gezira Journal of Health Sciences, 2013)
“The knowledge which a man can use is the only knowledge which has life and growth in it and coverts itself into practical power. The rest hangs like dust around the brain or dies like rain off stone”. Froude (1818-1894). Practice without theory is blind. Theory without practice is sterile. Lenin (1870-1924). The prime goal of medical education is to ensure the graduation of doctors who are equipped with knowledge, skills and attitudes that enable them to manage health problems in individuals, families and the community; as well as to help in creating a healthy environment at these levels.